ADVANCING PHILANTHROPY FOR OPHTHALMOLOGY IN INDONESIA: UNLEASHING THE POWER OF GIVING FOR VISION CARE - Visnu, Jodi (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Health philanthropy plays a crucial role in supporting charitable activities in the field of ophthalmology. The Indonesian Ophthalmologists Association (PERDAMI) has been actively engaged in various social initiatives to improve eye care services. However, it is imperative to consider long-term sustainability in funding to ensure the continuity of philanthropic efforts. Additionally, the recent regulatory changes in Indonesia highlight the need for philanthropic practices to comply with legal frameworks. This study presents the key highlights of a social-entrepreneurship session presented at the 48th Annual Scientific Meeting of the PERDAMI in August 2023, with aim to emphasize the importance of collaboration among stakeholders involved in ophthalmic philanthropy, including professionals, institutions, and grantors. The future sustainability of vision care is vital, and it requires the exploration of innovative funding models, the promotion of public-private partnerships, and the cultivation of a culture of giving. By raising awareness of this issue and incorporating it into strategic planning, stakeholders can work towards ensuring the availability and accessibility of quality eye care services in Indonesia. In conclusion, this study highlights the importance of integrating collaboration, needs assessment, good governance, and sustainability considerations in health philanthropy practices within Indonesian ophthalmology. These efforts will help shape the future of vision care and empower the PERDAMI to deliver meaningful and lasting impact in eye health.